Four‐Photon Greenberger–Horne–Zeilinger Entanglement via Collective Two‐Photon Coherence in Doppler‐Broadened Atoms. Issue 4 (22nd February 2021) - Park, Jiho; Kim, Heonoh; Moon, Han Seb
Abstract: Bright, entangled multiphoton sources based on atom–photon interactions are an essential requirement in the realization of several quantum information and quantum computation schemes based on photonic quantum systems. Here, a four‐photon polarization‐entangled Greenberger–Horne–Zeilinger (GHZ) state obtained from Doppler‐broadened atomic ensembles of 87 Rb atoms is experimentally demonstrated. Owing to collective two‐photon coherence in the Doppler‐broadened cascade‐type atomic system, the setup enables the generation of robust four‐photon GHZ states with a fidelity of 82.1% and a measured four‐photon average coincidence rate of 0.58 s −1 . It is believed that the generation of such bright and stable multiphoton GHZ states from atomic media is an important step toward realizing photonic quantum computation and practical quantum networks based on atom–photon interactions. Abstract : The generation of bright and stable multiphoton Greenberger–Horne–Zeilinger (GHZ) states from atomic media is an important step toward realizing photonic quantum technology based on atom–photon interactions. This work demonstrates a quite promising way of achieving the four‐photon GHZ states from atomic ensembles with a fidelity of 82.1% and a measured four‐photon counting rate of 0.58 s −1 .